Hepatoprotective Effect of Padina gymnospora in Albino Wistar Rat; A Biochemical and Histopathological Studies - Sarkar, Tanima Debnath; Muthulingam, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The methanolic extract of brown algae, Padina gymnospora (PG) was tested for hepatoprotective properties against paracetamol (acetaminophen, APAP)-induced liver damage in male albino Wistar rat through in-vitro model. Liver is damaged by the variation of serum enzymatic and biochemical markers, such as serum glutamate oxaloacetate transaminase (SGOT or AST), serum glutamate pyruvate transaminase (SGPT or ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), gamma-glutamyl transferase (GGT), bilirubin, albumin, and lipid peroxidation and antioxidant status were measured by SOD and SDH. The study found that PG caused dose-dependent histopathological changes in the liver and kidney of the rats. While low doses caused minimal alterations, higher doses resulted in significant tissue damage. This suggests that, despite its therapeutic potential, careful consideration is needed regarding dosage to ensure safety. Acute toxicity studies revealed that the LD50 value exceeded 3 g/kg body weight. These results indicate that the methanolic extract of PG contains active compounds with antioxidant, anti-inflammatory, detoxification support, liver regeneration, cholesterol regulation, prevention of liver fibrosis and hepatoprotective effects against high doses of paracetamol-induced hepatotoxicity [Fig. 1].